Diorganotellurium(IV) Dihalide Complexes with Bidentate Schiff Base Ligands—Part-I - Srivastava, Shekhar; Singh, Deepa (Asian Journal of Chemistry, 2010)
Sixty molecular adducts of organotellurium(IV) with bidentate Schiff base ligands of the type RR1 TeX.SB have been prepared and analysed to determine their structure by various physico-chemical techniques, i.e., elemental analysis, molar conductivity, IR and X-ray photoelectron spectroscopy.